Persistent Müllerian duct syndrome with testicular malignancy and unilateral seminal vesicle agenesis - Onur, Mehmet Ruhi; Poyraz, Ahmet Kursad; Kocakoç, Ercan; Orhan, Irfan (My University, 2011)
A 27-year-old male presented to our clinic for evaluation after operation which was made for a malignancy originated from undescended testis. Operation had revealed abdominal mass located right lateral to bladder originated from right testis. There were no additional findings at operation note. Pathology of specimen was mixed germ cell tumor consisting of embryonal carcinoma, yolk sac tumor and seminoma. Radiologic evaluation ultrasonography (US) showed a solid mass posterior to the bladder with a central cystic component and a hypoechoic oval shaped solid structure on the left side of this mass. Between these masses there was a hypoechoic band like structure. Magnetic resonance imaging (MRI) confirmed the presence of these masses. Four years after operation laboratory results revealed increased AFP levels and patient had exploratory laparotomy since a pelvic mass was seen on MRI and positron emission tomography (PET). Histopathologic diagnosis of tumor was embryonal carcinoma. © 2010 Elsevier Ireland Ltd.
Keywords: Magnetic resonance imaging; Persistent Müllerian duct; Seminal vesicle; Testicular malignancy; Ultrasonography